IMPACT OF MACROECONOMIC VARIABLES AND GLOBAL STOCK INDICES ON THE INDONESIAN COMPOSITE INDEX (IHSG): 2017–2023 - Anggrainy Putri Ayuningrum; M. Zuyyin Alifiadin; Meliza Meliza; M. Nuskan Abdi; Muhammad Maulidin Fachrur; Fitri Amalinda Harahap (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study analyzes the influence of macroeconomic variables and global stock indices on the IHSG during 2017–2023. The research is motivated by IHSG fluctuations amid changes in inflation, interest rates, exchange rates, and global market dynamics, reflecting investor responses to both domestic and international economic conditions. Prior studies have produced inconsistent results, highlighting the need for further investigation.METHODOLOGY - This research applies a quantitative approach using secondary monthly data from January 2017 to December 2023, totaling 84 observations. The independent variables consist of inflation, interest rates, exchange rates, the Hang Seng Index, and the Nikkei 225 Index, while the IHSG serves as the dependent variable. Data analysis includes classical assumption tests, multiple linear regression, model feasibility testing, and partial hypothesis testing using the t-test.FINDING - The findings reveal that inflation and the Nikkei 225 Index have a positive and significant effect on the IHSG, whereas the exchange rate has a negative and significant impact. Interest rates and the Hang Seng Index show positive and negative relationships, respectively, but are not statistically significant. These results suggest that domestic price stability and Japan’s economic conditions significantly influence the Indonesian stock market, while exchange rate volatility tends to weaken IHSG performance